Evaluation Of Football Refereeing System In The East Oku District Association - Harto, Eko Agus Sugi; Fikri, Aprizal; Muslimin, Muslimin; Hidayat, Arif; Hardiyono, Bayu (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2025)
This study aims to evaluate the soccer refereeing management system in the East OKU Regency Association using the CIPP (Context, Input, Process, Product) evaluation model. An effective refereeing system is essential in maintaining the quality and integrity of football matches at the local level. The method used is descriptive qualitative with data collection through observation, interviews, and documentation. The results showed that although the organizational structure and implementation of referee duties were in place, there were still significant obstacles such as limited continuous training, lack of systematic performance evaluation, and lack of technological support and awards for outstanding referees. The context evaluation revealed the social pressure that referees experience during matches, while the input and process evaluations indicated the need for improvements in human resource management and coordination between regions. Refereeing management products have made a positive contribution, but the consistency of referee quality still needs to be improved. This research recommends the development of continuous training programs, the implementation of a structured performance evaluation system, and the provision of incentives to strengthen football refereeing management in the regions. These findings can serve as a reference for other district soccer associations in improving the quality of refereeing.